Reinforced Microwave - Cured Acrylic Resin Denture Base Material with Glass Fibers - Radhwan H. Hasan; Mohammed A Abdulla (University of Mosul, College of Dentistry, 2010)
AIMS: To evaluation the Effect of adding glass fibers on the transverse strength and the levels of the residual monomer of specially formulated acrylic resin to be cured by microwave and heat cured acryl-ic resin denture base materials. MATERIALS AND METHODS: The materials were used in this study heat cured acrylic resin and microwave cured acrylic resin which is formulated to be cured by microwave energy( Acronacrylic resin). Thirty two samples were prepared for transverse strength test and divided into the following groups Control group (I) heat cured alone, group (II) microwave cured alone, the group (III) heat cured+fibers, group (IV) microwave cured+fibers the transverse strength was evaluated by using an Instron testing machine . Thirty two samples were prepared for residual mono-mer test and divided into four groups water bath and microwave cured with and without glass fibers, the residual monomer was evaluated by using ultraviolet visible spectrophotometer for seven days. RESULTS: Transverse strength test: Statistical Analysis of Variance(ANOVA) shows that there is significant differences at (p>0.0001)among the four groups and Duncan's multiple range test showed that microwave cured + fibers significantly higher transverse strength followed by heat cured +fibers, microwave alone, while heat alone shows significantly lowest transverse strength. Residual monomer test: Analysis of variance(ANOVA) for the four groups from the first day of immersion in water until 7th day shows that there are significant differences between the four groups in the all six days except the 7th day shows that there are no significant differences among the four groups for the level of the residual monomer. CONCLUSIONS: Microwave cured acrylic resin with glass fibers have signifi-cantly higher transverse strength than that of acrylic resin cured by water bath, also microwave cured acrylic resin have significantly lower residual monomer content from the 1st day of immersion when compared to that of water bath which show the same level of residual monomer at the 7th day of im-mersion